The autobiography of Mark Twain - Twain, Mark 1835-1910 (Office of English Language Programs, 2006)
The Autobiography of Mark Twain is the personal recollections of a great American author who wrote novels filled with adventure, humor, danger, and warmth. In these novels, he created characters that have become part of American culture: Tom, Huck Finn, Becky, Aunt Polly, and others